Path Analysis on the Determinants of Unwanted Pregnancy Among Adolescents in Madiun, East Java - Mutiara, Bunga; Budihastuti, Uki Retno; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2018)
Background: Unintended pregnancy is a worldwide problem that affects women, their families, and society. Unintended pregnancy can result from early marriage, contraceptive failure, non-use of contraceptive services, and, less commonly, rape. Consequences of unintended pregnancy includeÂ abortion with its long-term negative health effects including infertility and maternal death. This study aimed to examine the determinants of unwanted pregnancy among adolescents in Madiun, East Java, using path analysis model.Subjects and Method: This was a case control study conducted in Madiun, East Java, from April 4 to May 14, 2018. A sample of 150 adolescents was selected by fixed disease sampling, comprising 30 adolescents with and 120 adolescents without unwanted pregnancy. The dependent variable was unwanted pregnancy. The independent variables were knowledge, attitude, religiosity, sexual behavior, media exposure, parental role, and peer role. The data were collected by questionnaire and analyzed by path analysis run on Stata 13.Results: Unwanted pregnancy was directly determined by negative sexual behavior (b= 4.14; 95% CI= 2.83 to 5.45; p<0.001). It was indirectly determined by negative peer role, negative media exposure, negative attitude, parental role, better knowledge, and religiosity.Conclusion: Unwanted pregnancy is directly determined by negative sexual behavior. It is indirectly determined by negative peer role, negative media exposure, negative attitude, parental role, better knowledge, and religiosityKeywords: unwanted pregnancy, determinants, adolescents, path analysisCorrespondence:Â Bunga Mutiara, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: theo03theo@gmail.comJournal of Maternal and Child Health (2018), 3(3): 216-224https://doi.org/10.26911/thejmch.2018.03.03.06